1994
DOI: 10.1007/bf00191710
|View full text |Cite
|
Sign up to set email alerts
|

Drinking behavior and jaw muscle (EMG) activity in the pigeon (Columba livia)

Abstract: The relation between jaw movements and jaw muscle activity was examined during two different types of drinking in pigeons: "tip" and "rictus" drinking. The amplitude and duration of jaw opening is greater for "rictus" than for "tip" drinking, but both types involve individual cycles of jaw-opening and closing movements, organized into bouts. Cycle duration increases gradually over the initial portion of the bout and is relatively constant thereafter.Each drinking cycle is composed of an initial rapid jaw-openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This was evident in particular under the reversal condition ( Figure 5), when intermediate gape amplitudes emerged that were relatively infrequent or even absent under the baseline condition. Moreover, this finding, at the behavioral level, is consistent with a recent physiological analysis that related jaw muscle activity to eating and drinking response topography in the pigeon (Bout & Zeigler, 1994a, 1994b. This analysis showed that the substantial differences in gape amplitude and kinematic pattern that distinguish eating and drinking reflect primarily slight differences in the timing relations of the ensemble of opener and closer muscles.…”
Section: Mechanisms Of Pecking Response Modulationsupporting
confidence: 90%
“…This was evident in particular under the reversal condition ( Figure 5), when intermediate gape amplitudes emerged that were relatively infrequent or even absent under the baseline condition. Moreover, this finding, at the behavioral level, is consistent with a recent physiological analysis that related jaw muscle activity to eating and drinking response topography in the pigeon (Bout & Zeigler, 1994a, 1994b. This analysis showed that the substantial differences in gape amplitude and kinematic pattern that distinguish eating and drinking reflect primarily slight differences in the timing relations of the ensemble of opener and closer muscles.…”
Section: Mechanisms Of Pecking Response Modulationsupporting
confidence: 90%
“…From the mechanics of the jaw apparatus in the pigeon one might expect that the sequence of activities of upper and lower jaw opener and closer muscles are part of a pattern that can also be recognized in drinking. Although timing of jaw opener activities with respect to the jaw opening and closing movement is somewhat different, the pattern of activity is very similar to that of grasping [Bout and Zeigler, 1994b] (fig.¤5). As in grasping, the lower jaw opener (musculus depressor mandibulae) becomes active after the onset of the upper jaw opener muscle (PQP).…”
Section: Tongue Movementsmentioning
confidence: 57%
“…In the gape traces upward and downward movements represent jaw opening and jaw closing, respectively. Note the biphasic opening in the top gape trace, which is caused by a late onset of the lower jaw depressor [modified from Bout and Zeigler, 1994b;Van Gennip and Berkhoudt, 1994]. seen in filter-feeding birds. Mallards filter food from a waterflow through the beak (straining), which is generated by rhythmical jaw and tongue movements with a frequency up to 16 Hz.…”
Section: Tongue Movementsmentioning
confidence: 99%
“…Function: Contraction of this muscle rotates the lower jaw upwards. Its’ in vivo activity has not been examined directly ([27, 28]).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that columbiform birds are relatively conservative with respect to their pecking and drinking behaviour ([32]: page 2); however, they do exhibit variation in their feeding anatomy and ecological role. Most taxa (e.g., Columba , Streptopelia ) use their jaws primarily to garner loose seeds and grains and to gather twigs for nests; however, they will occasionally feed on insects and fruit [25, 27, 28, 30, 31, 42]. Other species, such as Duculua aenea , the Nicobar green imperial pigeon, are entirely fruit-eating and exhibit larger and more complex jaw muscles [25, 30, 40].…”
Section: Introductionmentioning
confidence: 99%